2016
DOI: 10.1167/iovs.16-19900
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Aqueous Humor Dynamics Assessing the Vault and the Pupil Diameter in Two Posterior-Chamber Phakic Lenses

Abstract: AH flow varies depending on the type of ICL implanted, whether it is implanted with an iridotomy or a central hole on the lens, the PD, and the vault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In a second study, these authors determined that the flow around the crystalline lens reached a maximum with a hole size of ~0.4 mm, indicating that “the current model, based on a central hole size of 0.36 mm, was close to ideal.”10 Recently, these authors also reported that “laser iridotomy is unnecessary from the viewpoint of theoretical aqueous circulation” in the presence of a central hole 11. Fernández-Vigo et al reported a full three-dimensional study based on computational fluid dynamics and concluded that “the circulation of aqueous humor is influenced by the type of lens implanted, being more physiological in the central hole model than in the one that requires an iridotomy.”12 These authors more recently provided an interesting theoretical paper describing a model of the circulation of aqueous humor in eyes with and without phakic refractive lenses 13…”
Section: Introductionmentioning
confidence: 99%
“…In a second study, these authors determined that the flow around the crystalline lens reached a maximum with a hole size of ~0.4 mm, indicating that “the current model, based on a central hole size of 0.36 mm, was close to ideal.”10 Recently, these authors also reported that “laser iridotomy is unnecessary from the viewpoint of theoretical aqueous circulation” in the presence of a central hole 11. Fernández-Vigo et al reported a full three-dimensional study based on computational fluid dynamics and concluded that “the circulation of aqueous humor is influenced by the type of lens implanted, being more physiological in the central hole model than in the one that requires an iridotomy.”12 These authors more recently provided an interesting theoretical paper describing a model of the circulation of aqueous humor in eyes with and without phakic refractive lenses 13…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena might represent a potential mechanical impact between the anterior side of the ICL and the posterior iris surface, thus influencing the function of the pupillae sphincter and dilator pupillae. Another explanation might relate to the aqueous humor; a study on aqueous humor dynamics using a computational simulation showed that the flow velocity of the aqueous humor was much greater if the pupil size was smaller after ICL V4c implantation [22]. Thus, aqueous humor resistance might also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results ( Fig 4 ), Dvoriashyna et al[ 29 ] described that most of AH flows through the PI, with almost all of it going through the PI for diameters larger than 150 μm. They described that the ideal size and location of a PI are influenced by various geometrical and fluid mechanical factors, the most relevant of which are the size of the hole, also analyzed by our group in a previous paper [ 19 ], and the length and height of the iris–lens channel. On the contrary, the location of the iridotomy only changes the total flow by 2% from an iridotomy placed in the middle of the PC to one placed peripherally, which is because the pressure is approximately uniform across the PC.…”
Section: Discussionmentioning
confidence: 99%
“…A three-dimensional full study simulation based on computational fluid dynamics (CFD) was performed with Ansys Fluent software (v16.2, ANSYS Inc. Pennsylvania, USA) enhancing our previous geometry model [ 19 ]. Simulations were conducted in steady laminar flow mode, setting a constant AH inflow rate of 2 μL/min (3.34 x 10–8 kg/s) and outflow boundary condition at the outlet section [ 19 ]. No-slip boundary conditions were prescribed on the solid surfaces.…”
Section: Methodsmentioning
confidence: 99%